(untitled) (Research, Society and Development, 2020)
To evaluate the action of photoinitiators on the microtensile resistance of adhesive systems and resins composed in bovine enamel. Forty dental fragments, with flat and smooth enamel surfaces, obtained from the coronary buccal face of healthy bovine incisors, were randomly assigned to 4 experimental groups (n = 10) according to the different adhesive systems and composite resins used: Group 1- Ambar APS + Vittra APS; Group 2- Ambar APS + Opallis; Group 3- Ambar + Vittra APS; Group 4- Ambar + Opallis. After composite restoration, the samples were sectioned to obtain toothpicks that were subjected to the microtensile test (1.0 mm/min). The data obtained were subjected to statistical analysis. The Kruskal-Wallis test revealed no significant differences between groups (p <0.05). Values ​​in MPa were: G1- 18.58 MPaa; G2 - 19.83 MPaa; G3- 19.87 MPaa; G4- 20.99 MPaa. The result of the Mann-Whitney test showed no significant differences due to the adhesive (Ambar Universal- 19.58 MPaa, Ambar APS Universal- 19.87 MPaa) and the composite resin used (Vittra APS- 19.52 MPAa, Opallis - 20.56 MPAa). The use of different photoinitiators in the composition of adhesive systems and restorative composites did not influence their adhesive resistance values ​​due to the standardization of the factors that influence their cure pattern.